Efficacy of theophylline in patients with syncope without prodromes with normal heart and normal ECG. (15th August 2019) - Brignole, Michele; Iori, Matteo; Solari, Diana; Bottoni, Nicola; Rivasi, Giulia; Ungar, Andrea; Deharo, Jean Claude; Guieu, Regis
Abstract: Background: Patients affected by syncope without or with very short (≤5 s) prodrome with normal heart and normal ECG have been seen to present low plasma adenosine levels. We investigated whether chronic treatment of these patients with theophylline, a non-selective adenosine receptor antagonist, results in clinical benefit. Methods: In a consecutive case-series of 16 patients (mean age 47 ± 25 years, 9 females) who had ECG documentation of asystolic syncope, we compared the incidence of syncopal recurrence during a period without and a period with tailored theophylline therapy. Results: During a median of 60 months before ECG documentation of the index episode, the patients had a median of 2 syncopes per year. During the 6 months of the study phase without therapy, the patients had a median of 2.6 syncopes per year, p = 0.63. During the 23 months of the study phase with theophylline, the patients had a median of 0.4 syncopes per year, p = 0.005 vs history and p = 0.005 vs no therapy. In the 13 patients who had an implantable loop recorder during both study phases, the incidence of asystolic episodes > 3 s decreased from 9.6 per year to 1.1 per year, p = 0.0007. During theophylline treatment, syncope recurred in 1/5 (20%) patients who had an idiopathic atrioventricular block as the index event versus 9/11 (81%) patients who had a sinus arrest, p = 0.005. Conclusion: Theophylline is effective in reducing syncopal burden in patients with syncope without prodromes with normal heart and normal ECG. Its efficacy is greater in those with idiopathic atrioventricular block. Highlights: Chronic oral theophylline therapy was effective in reducing syncopal burden. An adenosine-mediated mechanism is presumed to be responsible for pauses. Theophylline was more effective in patients with idiopathic AV block.